Current understanding of intracellular signalling pathways - the nuclear response to cAMP: role of transcription factor CREM - Lalli, Enzo; Foulkes, Nicholas S. (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 1996)
In eukaryotes, transcriptional regulation upon stimulation of the adenylate cyclase signalling pathway is mediated by a family of cAMP-responsive nuclear factors. This family consists of a large number of members which may act as activators or repressors. These factors contain the basic domain/leucine zipper motifs and bind as dimers to cAMP-response elements (CRE). The function of CRE-binding proteins is modulated by phosphorylation by several kinases. The ICER (inducible cAMP early repressor) protein is the only inducible member of this family. The induction of this powerful repressor is likely to be important for the transient nature of cAMP-induced gene expression. CRE-binding proteins have been found to play an important role in the physiology of the pituitary gland, in regulating spermatogenesis, in the response to circadian rhythms and in the molecular basis of memory.